PERAN WORLD TRADE ORGANIZATION (WTO) DALAM MENYELESAIKAN SENGKETA DAGANG ANTARA INDONESIA DAN AMERIKA SERIKAT TERKAIT LARANGAN IMPOR ROKOK KRETEK (DS406) - Atika Sari; Tuah Kalti Takwa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to examine the role of the World Trade Organization (WTO) in resolving the trade dispute between Indonesia and the United States in the DS406 case. The dispute arose from the implementation of the Family Smoking Prevention and Tobacco Control Act (FSPTCA) by the United States in 2009, which prohibited the importation of clove cigarettes. The policy was considered discriminatory because it directly affected Indonesian tobacco products. This research employs a qualitative approach using document analysis as its primary method. The theoretical framework focuses on the WTO's role as an international institution that regulates global trade through a rule-based system of dispute settlement. The analysis is conducted by examining official WTO documents and decisions issued through the Dispute Settlement Body (DSB). The findings indicate that the WTO plays a significant role in providing a dispute settlement mechanism that enables developing countries, including Indonesia, to defend their rights and interests more fairly within the global trading system. The WTO ruling in the DS406 case concluded that the United States' policy violated the principle of non-discrimination by treating Indonesian imported products less favorably. Kata kunci: World Trade Organization (WTO), Dispute Settlement Body, Trade Dispute, Clove Cigarettes, Non-Discrimination Principle, DS406.